2019
DOI: 10.3221/igf-esis.51.12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of static mean stresses on the fatigue behavior of 2024 aluminum alloy under multiaxial loading

Abstract: Axial alternating stress controlled fatigue tests with superimposed static torsional mean stress and shear alternating fatigue tests with superimposed static tensile mean stress are represented. The material used in the current experimental investigation is 2024 aluminum alloy. A decrease in the fatigue life of the material was observed with an increase in the shear and static tensile stresses. Marin and modified Crossland methods are analyzed by means of the available experimental data. The two modifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Fatigue curves are often represented using the well‐known Basquin equations: σ a = σ′ f · (2 N ) b (refer to, e.g., previous papers 62–65 ). The equation can be employed to derive the Basquin parameters σ′ f and b .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue curves are often represented using the well‐known Basquin equations: σ a = σ′ f · (2 N ) b (refer to, e.g., previous papers 62–65 ). The equation can be employed to derive the Basquin parameters σ′ f and b .…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue curves are often represented using the wellknown Basquin equations: σ a = σ 0 f Á(2N) b (refer to, e.g., previous papers [62][63][64][65] ). The equation can be employed to derive the Basquin parameters σ The comparison between the model predictions and the experimental results is visually presented in Figure 12, providing an insightful evaluation of the model's predictive accuracy when compared to experiments.…”
Section: Fatigue Testingmentioning
confidence: 99%
“…In pure torsion, the fracture is perpendicular to the rod axis (Fig. 2 d) In the article [37], the authors considered multiaxial fatigue models and compared them based on the results of biaxial nonproportional tests with a constant component of the shear and normal loading axes. Among the models, the most accurate is the modified Sines++ model.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
“…In addition, it is also important to check the applicability of models for notched and cracked bodies. In previous work, the Marin, modified Crossland and Sines models were compared by using non-proportional fatigue test data (with superimposed static mean stress) of 2024 aluminum alloy [37]. As a result, it was shown that the modified Sines method described the experimental data in the most accurate way.…”
mentioning
confidence: 99%
“…Параметры нагружения (изменение соотношения амплитуд напряжений, сдвига фаз, соотношения частот нагружения, средних напряжений в цикле и т.д.) могут существенно влиять на усталость материала [11][12][13][14][15][16][17][18]. Для описания усталостного поведения используются различные модели многоосной усталости, которые можно разделить на три группы: основанные на напряжении, деформации и энергии [19].…”
Section: Introductionunclassified